2015
DOI: 10.1007/s10877-015-9786-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensor fusion methods for reducing false alarms in heart rate monitoring

Abstract: Automatic patient monitoring is an essential resource in hospitals for good health care management. While alarms caused by abnormal physiological conditions are important for the delivery of fast treatment, they can be also a source of unnecessary noise because of false alarms caused by electromagnetic interference or motion artifacts. One significant source of false alarms is related to heart rate, which is triggered when the heart rhythm of the patient is too fast or too slow. In this work, the fusion of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The AD configuration most suited to a clinical need can then be hard-coded and integrated into the clinical workflow for real-time implementation. For example, some recently developed AD algorithms leverage sensor fusion for motion artifact removal while deriving the heart rate (HR) [33][34][35][36][37]. The implementation of these AD and CED algorithms within the framework simply requires modifying their interfaces to comply with the CRM.…”
Section: Common Reference Modelmentioning
confidence: 99%
“…The AD configuration most suited to a clinical need can then be hard-coded and integrated into the clinical workflow for real-time implementation. For example, some recently developed AD algorithms leverage sensor fusion for motion artifact removal while deriving the heart rate (HR) [33][34][35][36][37]. The implementation of these AD and CED algorithms within the framework simply requires modifying their interfaces to comply with the CRM.…”
Section: Common Reference Modelmentioning
confidence: 99%
“…Review on fusion method for stress classification From Table 1, very few studies were found to have used fused HRV, for stress classification. However, some related studies were found using HRV in the fusion method as a sensor for detecting false alarms during patient monitoring [19,38]. It should be noted that there has been no study that used salivary cortisol in the fusion.…”
Section: Tablementioning
confidence: 99%
“…Sensitivity is the probability that an event tested will receive a positive test result [72]. It also defined as the ratio of the TP to the total number of events, and is given by: (19) Meanwhile, the specificity, (also known as the true negative rate) is the probability that an event that is tested will receive a negative test result [72]. It is also defined as the ratio of the TN (true negatives) to the total number of non-events, and is given by:…”
Section: Fig 7 Confusion Matrixmentioning
confidence: 99%
“…Technical issues such as artifact, electromagnetic interference and poor recording quality present another issue in interpreting alarms. Borges and Brusamarello employed ML in conjunction with other methods to fuse physiological data to address the first two problems [11]. They found that the ML/neural networks approach to the issue produced the best results i.e.…”
Section: Reducing False Alarmsmentioning
confidence: 99%